Research and publications in Islamic perspective (part 5: innovation and creativity) - Khedher, Akram M Z M (Kulliyyah of Information and Communication Technology, IIUM, 2024)
This is the fifth article in the series titled "Research and Publications in Islamic Perspective." While the first article discussed the introduction to this subject, the second article focused on the experimental results of the research, the third article discussed the presentation issues that are necessary in any research, and the fourth article discussed the importance of publishing research work and sharing one's knowledge with others, in this article (part 5), we are going to talk about the innovation and creativity that goes into conducting any research.